Phylum Onychophora Grube, 1853. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Mayer, Georg; Oliveira, Ivo De Sena (Zootaxa, 2011)
-